Pengaruh Perputaran Kas, Perputaran Persediaan Dan Perputaran Piutang Terhadap Profitabilitas : Studi Kasus Pada Koperasi Pegawai Perum Bulog NTB (Kopel) Periode 2019-2023 - Pitriyani, Putri Rahayu; Pusparini, Herlina (Jurnal Ilmiah Global Education, 2025)
This study aims to examine the Effect of Cash Turnover, Inventory Turnover and Receivables Turnover on Profitability at the NTB Bulog Employee and Pensioner Cooperative (Kopel NTB) for the 2019-2023 Period. The research method used is quantitative with an associative approach, using secondary data in the form of the NTB Kopel financial report. The research sample used was the NTB Kopel financial report for 5 periods, namely 2019-2023. The results of this study indicate that cash turnover, inventory turnover and receivables turnover have not been proven to have a significant effect on profitability. This study contributes to increasing understanding of the factors that influence cooperative Profitability, especially Cash Turnover, Inventory Turnover and Receivables Turnover at the NTB Bulog Employee and Pensioner Cooperative (Kopel NTB).